Temozolomide and/or Erlotinib in the Treatment of Lung Cancer Patients With Progressive Central Nervous System Metastases - Lukas, Rimas V (2012)
BACKGROUND: Patients with lung cancer who develop brain metastases have a poor prognosis. Those patients with progressive brain metastases tend to have a dismal prognosis. Currently, there is no standard of care for the treatment of these patients. METHODS: In this manuscript, we present a retrospective evaluation of 10 patients treated at our institution with a combination of temozolomide and/or erlotinib after disease progression in the central nervous system following radiation therapy. RESULTS: Median overall survival was 28 weeks. Median time to progression in the central nervous system was 14 weeks. Median time to progression systemically was 7.5 weeks. Some patients demonstrated prolonged stability of disease. CONCLUSIONS: A palliative regimen of temozolomide and/or erlotinib could be considered in progressive central nervous system metastases from lung cancer.